1998
DOI: 10.2337/diacare.21.10.1652
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight, Adult Weight, and Girth as Predictors of the Metabolic Syndrome in Postmenopausal Women: The Rancho Bernardo Study

Abstract: Low birth weight coupled with adult obesity is a strong determinant of the metabolic syndrome in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
1
4

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(85 citation statements)
references
References 33 publications
3
77
1
4
Order By: Relevance
“…In many population studies, reduced fetal growth has been reported to be a risk factor for insulin resistance and type 2 diabetes [2,4,9,[15][16][17]. In particular, subjects who were small or thin at birth but subsequently developed obesity in childhood or in adulthood have the highest risk of developing insulin resistance [9,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In many population studies, reduced fetal growth has been reported to be a risk factor for insulin resistance and type 2 diabetes [2,4,9,[15][16][17]. In particular, subjects who were small or thin at birth but subsequently developed obesity in childhood or in adulthood have the highest risk of developing insulin resistance [9,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Low birth weight is considered to indicate undernutrition of the fetus in the uterus. Many epidemiological studies supported the hypothesis that those born with low birth weight were at an elevated risk of developing type 2 diabetes and other disorders during adulthood (3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 92%
“…Birth weight was positively associated with HDL cholesterol in postmenopausal women from the Rancho Bernardo Study, 7 but was unrelated to HDL cholesterol in men studied by Byberg et al 8 Birth weight was inversely associated with TG in boys and girls : number of days prior to the next menses HDL cholesterol: high-density lipoprotein cholesterol BMI: body mass index 0.38, p = 0.003) after controlling for age and group status. However, blood was drawn again on the day 11 of the menstrual cycle.…”
mentioning
confidence: 97%